Analisis Perbandingan Quantity Take Off (QTO) Beton Menggunakan Metode Building Information Modelling (BIM) dan Metode Konvensional (Studi Kasus : Proyek Kantor PNM Cabang Jember) - Amri, Salim Isfayama; Hardyanti, Nurandani; Sumiyati, Sri (Jurnal Profesi Insinyur Indonesia, 2023)
Along with the world of construction that is growing, the stakeholders involved in it are trying to find methods and technologies that can make the activities contained in construction projects more efficient. Building Information Modeling (BIM) is one of the most widely applied technological developments in the world of construction. One of the benefits of implementing BIM is that it can produce Quantity Take-Off (QTO) data output based on the 3 Dimensional model that has been created. This research examines the PT Permodalan Nasional Madani Branch Office Building Construction Project in Jember City which performs QTO calculations using 2 methods, namely the conventional method and the BIM method. The purpose of this study is to find out the results of the calculation of the QTO of the Conventional Method and the BIM Method, then to compare the results of the calculation of the QTO of the Conventional Method and the BIM Method, and to analyze the reasons for the differences in the results of QTO calculations on the Conventional Method and the BIM Method. The conventional method of performing calculations is using Ms.Excel software with reference to 2D drawings from AutoCAD. The BIM method uses Autodesk Revit software by performing 3D modeling which is directly integrated with the quantity calculation. The QTO calculation is carried out on the need for concrete materials in the superstructure (columns, beams and slabs) of the building. The results of QTO Concrete using the BIM method on column work 41.59 m³, beams 33.29 m³, and floor slabs 154.39 m³. The total QTO of concrete for the superstructure using the BIM method is 229.23 m³. The results of QTO Concrete using the Conventional method on column work 44.36 m³, beams 58.79 m³, and floor slabs 154.54 m³. The total QTO of concrete for the superstructure using the conventional method is 257.68 m³. The difference in the QTO results of the BIM and conventional methods for column work is 6.24%, beams are 43.37%, floor plans are 0.12%. The difference in the highest QTO value is in the beam structure item. The total difference in volume of concrete between the conventional method and the BIM method is 28.45 m³ or 11.04%. The reason for the difference in QTO results between the BIM and Conventional methods is due to the double calculations in the Conventional method at each intersection point between columns, beams and plates. Whereas with the BIM method every meeting will be calculated only on one of the elements with the order of domination of the calculation from the highest, namely plate, column, plate.